The Effects of Athletes' Imposter Syndrome Tendency on Achievement Goal Orientation and Regulatory Focus - Ki-Yeon Kim; Yong-Hyun Lee (Korea Institute of Sport Science, 2023)
PURPOSE This study aimed to verify the influence of imposter syndrome tendencies in athletes on their achievement goal orientation, and regulatory focus. METHODS Data collected from 413 athletes through surveys were analyzed using SPSS version 27.0 and AMOS version 21.0 to assess reliability and validity, conduct independent sample t-tests, perform correlation analysis, and conduct multiple regression analyses. RESULTS The findings revealed significant sex-based differences in imposter syndrome tendencies, achievement goal orientation, and regulatory focus. Moreover, significant correlations were observed between sub-factors of imposter syndrome, achievement goal orientation, and regulatory focus. Imposter syndrome tendencies had varying effects on achievement goal orientation, with the discount factor significantly influencing approach orientation, the fake factor significantly affecting avoidance orientation, and fear factors significantly impacting self-avoidance. Additionally, imposter syndrome tendencies influenced regulatory focus, as the discount factor significantly affected both promotion focus and prevention focus, while fake and fear factors significantly influenced prevention focus. CONCLUSIONS This study underscores the importance of athletes' imposter syndrome tendencies as significant contributors to psychological variables related to motivation, including achievement goal orientation and regulatory focus.